Upstart Puzzles Sampling the Goods. - Shasha, Dennis (Communications of the ACM, 2023)
The article discusses several scenarios involving questions regarding sampling, information theory, and different types of packages located inside shipping containers, and it mentions time management in relation to inspections of packages. Information theory is addressed, along with solutions and strategies for finding 1,000 good packages in containers.